"We just do us": How Black teachers co-construct Black teacher fugitive space in the face of antiblackness. Issue 3 (16th April 2023) - Stovall, Jessica Lee; Mosely, Micia
ABSTRACT: This article presents findings from an empirical study that sought to understand how Black teachers collectively built a Black affinity space in response to the antiblackness they faced in their school sites. Analyses of interview and participant observation data point to the importance of Black teachers creating spaces reminiscent of a homeplace, where they can speak and act with their full selves through play, humor, and various expressions of Blackness. The article argues that the concept of affinity spaces is insufficient to describe what the teachers in the study collectively built. Instead, we draw on notions of fugitivity from Black Studies to theorize this space as a pro-Black fugitive space. We argue that these Black teacher fugitive spaces are rehumanizing and sustaining for Black teachers, offering implications for Black teacher support and retention.